Demonstration of negative refraction induced by synthetic gauge fields - Yang, Yihao (2022)
Negative refraction is a counterintuitive wave phenomenon that has inspired the development of metamaterials and metasurfaces with negative refractive indices and surface phase discontinuities, respectively. Recent theories have proposed an alternative mechanism for negative refraction: Synthetic gauge fields, induced by either dynamical modulation or motion, can shift a material’s dispersion in momentum space, forcing a positive refractive index medium to exhibit negative refraction above a certain threshold. However, this phenomenon has not previously been observed. Here, we report on the experimental demonstration of gauge field–induced negative refraction in a twisted bilayer acoustic metamaterial. The synthetic gauge fields arise in a projected two-dimensional geometry and can be continuously tuned by varying the wave number along the third dimension. Gauge field–induced waveguiding with backward-propagating modes is also demonstrated in a trilayer configuration. These results introduce a mechanism for performing wave manipulation in artificially engineered materials.